South African EUCAARI measurements: seasonal variation of trace gases and aerosol optical properties - L. Laakso; V. Vakkari; A. Virkkula; H. Laakso; J. Backman; M. Kulmala; J. P. Beukes; P. G. van Zyl; P. Tiitta; M. Josipovic; J. J. Pienaar; K. Chiloane; et al. (Atmospheric Chemistry and Physics, 2012)
In this paper we introduce new in situ observations of atmospheric aerosols, especially chemical composition, physical and optical properties, on the eastern brink of the heavily polluted Highveld area in South Africa. During the observation period between 11 February 2009 and 31 January 2011, the mean particle number concentration (size range 10–840 nm) was 6310 cm3 and the estimated volume of sub-10 μm particles 9.3 μm3 m−3. The aerosol absorption and scattering coefficients at 637 nm were 8.3 Mm−1 and 49.5 Mm−1, respectively. The mean single-scattering albedo at 637 nm was 0.84 and the Ångström exponent of scattering was 1.5 over the wavelength range 450–635 nm. The mean O3, SO2, NOx and H2S-concentrations were 37.1, 11.5, 15.1 and 3.2 ppb, respectively. The observed range of concentrations was large and attributed to the seasonal variation of sources and regional meteorological effects, especially the anticyclonic re-circulation and strong winter-time inversions. In a global context, the levels of gases and particulates were typical for continental sites with strong anthropogenic influence, but clearly lower than the most polluted areas of south-eastern Asia. Of all pollutants observed at the site, ozone is the most likely to have adverse environmental effects, as the concentrations were high also during the growing season. The measurements presented here will help to close existing gaps in the ground-based global atmosphere observation system, since very little long-term data of this nature is available for southern Africa.